Analisis Perbandingan Efisiensi Kinerja Mesin Pencacah Rumput 6.5 HP dan 5.5 HP menggunakan 4 Mata Pisau - Eki Sripratama; Budi Harjanto (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2026)
This study aims to analyze the comparative performance efficiency of grass chopper machines powered by 6.5 Hp and 5.5 Hp using four blades under constant rotational conditions of approximately 2300 rpm. The research employed an experimental method with a comparative design. Data were collected through direct testing of both machines, focusing on effective capacity, fuel consumption, time efficiency, and chopping quality. Each test was repeated five times using measuring instruments including a scale, stopwatch, measuring cup, and ruler. The results show that the 6.5 Hp machine achieved a higher average effective capacity of 196.27 kg/h and time efficiency of 3.26 kg/min compared to the 5.5 Hp machine, which produced 194.7 kg/h and 3.24 kg/min. However, the 5.5 Hp machine demonstrated better fuel efficiency at 0.066 liters/kg, while the 6.5 Hp machine consumed 0.080 liters/kg. The chopping quality of both machines was relatively uniform with no significant differences observed. These findings indicate that engine power affects capacity and working speed, while lower power engines tend to be more fuel efficient. Therefore, machine selection should consider operational needs, scale of use, and fuel efficiency.